Evaluation and correlation for growth, yield and quality traits of ridge gourd (Luffa acutangula) under arid conditions - CHOUDHARY, B R; KUMAR, SURESH; SHARMA, S K (The Indian Journal of Agricultural Sciences, 2014)
Landraces of ridge gourd [Luffa acutangula (Roxb.) L.] are spread over a wide range of environments in India and their fruits are consumed as vegetable. The dry fruits of six commonly grown genotypes were collected from different parts of Rajasthan. The collected materials were evaluated during summer season of 2011 and 2012 under hot arid conditions of western Rajasthan for growth traits, flowering, yield, yield components and quality traits. The evaluated genotypes showed significant variation for most of these traits, except pH of flesh. Average number of fruits per plant was the highest in AHRG 29 (21.75) and the lowest in AHRG 27 (17.30), which had the highest fruit length (27.26cm), fruit diameter (5.13cm), ovary length (8.06 cm) and fibre content (1.96 g/100g edible portion). The highest fruit hardness was also recorded in AHRG 27 (4.91 kg/cm2), whereas the lowest in AHRG 29 (3.54 kg/cm2). Significant correlation coefficients among growth, flowering, yield, yield traits and quality traits were found. The marketable yield/plant had positive and highly significant correlation with fruit weight (0.834) and number of marketable fruit/plant (0.624) at phenotypic level. The results of this study could be used in breeding programs for improving local landraces of ridge gourd grown in Rajasthan, India.